Effect of Decentralization Strategy on Macroeconomic Stability in Thailand - Kanokpan Lao-Araya (Asian Development Bank (ADB), 2002)
"This research study examines how the Thai central government can finance decentralization and make local governments accountable for their own finances. The Thai government's medium-term fiscal stance is not conducive to planned fiscal decentralization, and local governments will not immediately assume responsibility for providing public services previously provided by the central government. This study proposes that the central government must improve revenue collection efficiency without hindering economic growth by gradually increasing the value added tax rate over the medium term. Thailand has adopted an unbalanced approach to fiscal decentralization. Local governments are guaranteed revenue from transfers from the central government but need not assume increased responsibility for providing public services. This encourages local authorities to spend irresponsibly in expectation of bailouts by the central government. This study recommends that the Thai central government impose hard budget constraints on local governments."
hdl:11540/2044
Keywords: 330; Dezentralisierung; Öffentliche Finanzen; Steuerpolitik; Thailand